The Church, Gender and AIDS: What's Wrong with Patriarchy? - Pillay, Miranda N. (Missionalia, 2015)
Many women and children suffer in silence in cultures where patriarchy is condoned and defended as the natural order of things. The inferior status ascribed women and children where patriarchy is imbued as hypernormative, render them vulnerable to contracting the HI-virus as the case study cited here reveals. While government and civil society, including the church, sometimes react when violence against women and/or children end in the victim of violence being killed, the argument made here is that a pro-active response may go a long way such as addressing the patriarchy of our (Christian) faith.